1996
DOI: 10.1021/es950937d
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Mercury Concentrations Associated with Geologically and Anthropogenically Enriched Sites in Central Western Nevada

Abstract: This paper documents the atmospheric mercury concentrations above anthropogenically contaminated and naturally enriched sites in central western Nevada. Atmospheric mercury concentrations were measured at five representative regional sites (1.2−7.5 ng/m3) and two anthropogenically contaminated areas (13−866 ng/m3) in the Carson River Superfund Site. The highest regional concentrations were measured at the Steamboat Geothermal area, where mercury mineralization occurs naturally. Concurrent with atmospheric samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Seigneur et al (44) suggested that reactions with gaseous sulfur species were also possible. The geothermal brines at the SBMM contain high concentrations of SO4, chloride, and bromide (34), and HCl was measured in the air at the site (21). In addition, high emissions of H2S and NH3 have been reported in gases at the site (24).…”
Section: Resultsmentioning
confidence: 99%
“…Seigneur et al (44) suggested that reactions with gaseous sulfur species were also possible. The geothermal brines at the SBMM contain high concentrations of SO4, chloride, and bromide (34), and HCl was measured in the air at the site (21). In addition, high emissions of H2S and NH3 have been reported in gases at the site (24).…”
Section: Resultsmentioning
confidence: 99%
“…We assumed that meteorological effects are slight inside an enclosed flux chamber and estimated the contribution of the soil gas Hg ø which was displaced by the rain water as follows: It is more likely that the second process listed above has a major contribution. The soil analyses [Gustin, et al, 1996, this issue (a)] show that most of the soil plots contained a large proportion of total Hg as Hg ø, ---30-50%. Since the soil mer---2 cury flux over prerain dry soils was relatively low (---40 ng m h-•), we propose that before the rain, most of the Hg ø in the soils was adsorbed to dry soil particle surfaces and not directly available for emission.…”
Section: Discussionmentioning
confidence: 99%
“…Mercury exists in soils in several forms, many of which (particularly Hg ø) exhibit relatively high elevated vapor pressures at background temperature. The primary sources of Hg in soils which have not been with temperature, and many studies have reported exponential relationships between temperature and emission rates for background, contaminated, and geologically enriched soils as well as buried wastes [e.g., Lindberg and Turner, 1977;Lindberg et al, 1979;Xiao et al, 1991;Lindberg et al, 1995;Gustin et al, 1996]. Because of the strong temperature effect, few other relationships have been as well documented, and the recent suggestions of a direct effect of solar radiation on fluxes are complicated by indirect temperature effects frdm soil heating [Gustin et al, 1996;Carpi and Lindberg, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, considerable progress in understanding mercury geochemistry at such sites has been made with the development of interfacial mercury flux measurement technology (Ferrara et al, 1998a;Ferrara et al, 1998b;Gustin et al, 1996;Nacht et al, 2004;Gustin, 2003;Engle et al, 2001). Mercury emission rates from these Hg-enriched areas were found to be greater than previously estimated, indicating that these sources may be more significant contributors of mercury to the atmosphere than previously realized (Gustin et al, 2000;Gustin, 2003;Engle et al, 2001;Wang et al, 2005, Wang et al, 2007a, Wang et al, 2007bCoolbaugh et al, 2002;Feng et al, 2005).…”
Section: Introductionmentioning
confidence: 99%